2016
DOI: 10.1097/iae.0000000000000616
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Dexamethasone Implant for the Treatment of Refractory Macular Edema in Retinal Vascular Diseases

Abstract: The dexamethasone implant improved macular edema in refractory cases resulting in statistically significant improvements in best-corrected visual acuity and central macular thickness that remained stable to 3 months and 6 months, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 16 publications
1
33
1
1
Order By: Relevance
“…In a real-life study, IOP elevations of at least 10 mm Hg were reported in 7.9% of eyes [24], very similar to the rate we found in the current study (7.4%). On the other hand, some studies reported higher frequencies of IOP elevations: for example, an elevation of at least 20 mm Hg was registered by Alshahrani et al [15] in 26% of eyes, and an elevation of at least 25 mm Hg was reported by Bonnin et al [16] in 21% of eyes. Although these different percentages among studies may be due to variations in patient selection or the frequency of assessment, in most cases the authors found IOP elevations to be transient and amenable to topical treatment [18, 24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a real-life study, IOP elevations of at least 10 mm Hg were reported in 7.9% of eyes [24], very similar to the rate we found in the current study (7.4%). On the other hand, some studies reported higher frequencies of IOP elevations: for example, an elevation of at least 20 mm Hg was registered by Alshahrani et al [15] in 26% of eyes, and an elevation of at least 25 mm Hg was reported by Bonnin et al [16] in 21% of eyes. Although these different percentages among studies may be due to variations in patient selection or the frequency of assessment, in most cases the authors found IOP elevations to be transient and amenable to topical treatment [18, 24].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study from Spain with 58 patients, a mean gain of 7 letters was reported at 1 month [23]. Similarly good results were reported by a second Spanish group, with combined data from patients from Saudi Arabia; in this retrospective series of 53 eyes with DME ( n = 26) or refractory macular edema from central or branch retinal vein occlusion ( n = 27), the baseline BCVA of 0.89 ± 0.97 logMAR improved significantly to 0.61 ± 0.41 logMAR at the first month and 0.5 ± 0.46 logMAR at 3 months [15]. Likewise, improvements of similar magnitude at various time points were reported in retrospective series from France [16, 18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…특히, 덱사메타손 임플 란트(Ozurdex ® , Allergan, Irvine, CA, USA)는 한 번의 삽입술 로 6개월까지 유리체내에 존재하며 [15], 21.5-22.2%의 환자에서 3줄 이상의 시력 상승을 보고하고 있다 [13,16]. 이러한 덱사메타 손 임플란트는 항혈관내피세포성장인자치료에 비해 긴 작용 시 간과 함께 유사한 치료 효과를 보여주었고 [17,18], 항혈관내피세 포성장인자 치료에 반응하지 않는 난치성(refractory) 당뇨황반 부종 환자에게도 효과가 있는 것으로 알려지면서 [19,20], 당뇨황 반부종 환자에서 그 적응증을 넓혀 가고 있다. 당뇨황반부종에서 유리체황반경계면 이상은 흔히 발견되는데 약 27-34% 정도에서 망막전막이 동반되는 것으로 보고되고 있 다 [21,22].…”
unclassified